2016
DOI: 10.1016/j.tcm.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts for patients with treatment-resistant hypertension

Abstract: Treatment resistant hypertension (TRH) is defined as elevated blood pressure despite treatment with three properly dosed antihypertensive drugs, and is associated with adverse cardiovascular and renal outcomes and increased mortality. Treatment of patients with TRH focuses on maximizing the doses of antihypertensive drugs and adding drugs with complementary mechanisms of action, including a combination of angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers, calcium channel blockers, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
0
27
0
2
Order By: Relevance
“…[ 6 ] Although some randomized controlled trials (RCTs) have demonstrated the efficacy of spironolactone as a fourth-line therapy for patients with RH, there are no available high-quality, large-scale clinical trials to evaluate the efficacy and safety of spironolactone for RH. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Although some randomized controlled trials (RCTs) have demonstrated the efficacy of spironolactone as a fourth-line therapy for patients with RH, there are no available high-quality, large-scale clinical trials to evaluate the efficacy and safety of spironolactone for RH. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…For treatment of PA, surgical adrenalectomy is applied for patients with unilaterally increased aldosterone production [ 11 ], and patients with bilateral increased aldosterone production are treated with drugs such as MR antagonists (spironolactone or eplerenone) [ 12 ]. However, a small, but considerable subset of patients remain hypertensive despite administration of these drugs known as treatment-resistant hypertension (TRH), underscoring the need for development of a novel drug [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions with three different classes of antihypertensive agents, including a diuretic at the ideal dose, are necessary to achieve target values of BP in resistant hypertensive patients [ 10 , 15 , 20 , 27 , 28 ]. However, some resistant hypertensive patients, despite treatment with a three-drug regimen need at least four antihypertensive agents to gain adequate BP control [ 11 , 13 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the recommendations on research priorities published by Professor Iain Chalmers, [ 31 ] we can state that studies of the pathophysiology of RH emphasize persistent fluid retention, increased sodium sensitivity, excessive salt intake, hyperaldosteronism and a certain degree of renal dysfunction as common underlying causes that contribute to the hypervolemic state found in these patients [ 15 , 28 , 32 37 ]. On the other hand, RH patients may present different pathophysiological mechanisms in terms of etiology and so consistently demonstrated sympathetic nervous hyperactivity as evidenced by the measurement of 24-h urinary metanephrines, increased resting heart rate (HR) mainly during sleep, increased HR variability during 24-h spectral analysis with Holter monitoring, increased arterial stiffness inferred by pulse wave velocity and increased peripheral arterial resistance [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation